(untitled) (Research, Society and Development, 2025)
Menopause marks the end of the female reproductive period and is accompanied by intense hormonal, metabolic, and bodily changes, such as increased visceral fat, loss of lean and bone mass, and a higher risk of chronic diseases. This study aimed to analyze the main hormonal and body composition changes during menopause and their nutritional implications for women’s health and quality of life. This is a literature review based on articles published between 2014 and 2024 that addressed nutritional strategies targeted at this stage. The results indicated that a balanced diet rich in fruits, vegetables, lean proteins, whole grains, calcium, vitamin D, and phytoestrogens such as soy is beneficial for well-being and disease prevention. Dietary patterns such as the Mediterranean and DASH diets have shown positive effects on lipid profiles and body composition. Furthermore, supplementation with compounds such as mulberry leaf can help alleviate symptoms. It is concluded that the nutritionist has a fundamental role in individualizing behaviors and promoting healthy eating habits, making nutrition essential in the comprehensive care of menopausal women.